Influence of diode laser and warm air drying on the shear bond strength of Lithium di-silicate to Dentin. An in-vitro study - Riad, Mohamed; Othman, Hesham Ibrahim; Mohamed, Hussein Ramadan (Brazilian Dental Science, 2022)
Objective: The current study aimed to evaluate the effect of diode laser irradiation (980 nm) and warm air drying (50°C) on shear bond strength between Lithium di-silicate (IPS e.max; Ivoclar) and human dentin using both (Etch & Rinse) adhesive, Adper™ Single Bond 2 (3M ESPE) and (Self-etch) adhesive, Single Bond UniversalTM (3M ESPE) before adhesive polymerization. Material and Methods: 54 sound lower molars were sectioned to obtain flat dentinal surfaces. Specimens were divided into 2 equal groups (n=27): Group 1 (ER) and Group 2 (SE) according to bonding approach. Each subgroup was subdivided according to dentin surface treatment into 3 equal subgroups (n=9): Control (Co), Diode laser irradiation (L) and Warm air drying (W). All specimens were adhesively cemented to IPS e.max® CAD discs using RelyX™ Ultimate Clicker™(3M ESPE) resin cement. Samples were then subjected to pre-loading in a thermodynamic manner. All samples were tested for shear bond strength using computer-controlled material testing machine. Data analysis was performed using two-way (ANOVA) (p< 0.05) followed by pair-wise Tukey’s post-hoc tests. Results: In (SE) group, the subgroup (W) had the highest shear bond strength values followed by (Co) subgroup and the least was (L) subgroup with statistically significant difference. As for (ER) group, the subgroup (W) had the highest shear bond strength values followed by (Co) subgroup and the least was (L) subgroup with no statistically significant difference. Conclusion: Warm air drying for (SE) bonding approach increased shear bond strength of Lithium di-silicate to human dentin and can be introduced as a new effective protocol. KEYWORDS Adhesives; Diode laser; IPS e.max; Shear bond strength; Warm air drying.